2018
DOI: 10.1063/1.5030509
|View full text |Cite
|
Sign up to set email alerts
|

Magnetometric mapping of superconducting RF cavities

Abstract: A scalable mapping system for superconducting RF (SRF) cavities is presented. Currently, it combines local temperature measurement with 3D magnetic field mapping along the outer surface of the resonator. This allows for the observation of dynamic effects that have an impact on the superconducting properties of a cavity, such as the normal to superconducting phase transition or a quench. The system was developed for a single cell 1.3 GHz TESLA-type cavity, but can be easily adopted to arbitrary other cavity typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The rest of this review focuses on rf losses of Abrikosov vortices with normal cores [18]. Such vortices trapped by a random pinning potential of materials defects can bundle together, forming localized hotspots which have been revealed by temperature mapping of Nb cavities [30,79,80] and thin film structures [81,82], as well as by magnetic mapping [257][258][259]. Unlike hotspots caused by lossy materials defects, vortex hotspots can be moved or fragmented by temperature gradients produced by external heaters [119] or scanning laser [80,120,260,261] or electron [262,263] beams.…”
Section: Trapped Vorticesmentioning
confidence: 99%
“…The rest of this review focuses on rf losses of Abrikosov vortices with normal cores [18]. Such vortices trapped by a random pinning potential of materials defects can bundle together, forming localized hotspots which have been revealed by temperature mapping of Nb cavities [30,79,80] and thin film structures [81,82], as well as by magnetic mapping [257][258][259]. Unlike hotspots caused by lossy materials defects, vortex hotspots can be moved or fragmented by temperature gradients produced by external heaters [119] or scanning laser [80,120,260,261] or electron [262,263] beams.…”
Section: Trapped Vorticesmentioning
confidence: 99%
“…The HZB developed a temperature-and magnetic-fieldmapping system which can be applied to single-cells during the rf tests with a three-dimensional control over the ambient magnetic field using three sets of Helmholtz-coils [30]. Several measurements of 1DE16 with this set up installed were done.…”
Section: Measurements At Hzbmentioning
confidence: 99%
“…In particular, it was found that the size of trapped flux is affected by several different parameters, such as the cooldown conditions or material properties like RRR (residual resistivity ratio). This laid the basis for further, systematic investigations [1][2][3][4][5][6][7][8][9][10][11]. These methods have in common that the magnetic flux is observed indirectly-either by measuring its impact on the cavity performance or by measuring the impact of the incomplete Meissner transition on the ambient magnetic field or by small angle neutron scattering.…”
Section: Introductionmentioning
confidence: 99%